2012
DOI: 10.1088/0004-637x/756/1/82
|View full text |Cite
|
Sign up to set email alerts
|

On the Relativistic Precession and Oscillation Frequencies of Test Particles Around Rapidly Rotating Compact Stars

Abstract: Whether or not analytic exact vacuum (electrovacuum) solutions of the Einstein (Einstein-Maxwell) field equations can accurately describe the exterior space-time of compact stars still remains an interesting open question in relativistic astrophysics. As an attempt to establish their level of accuracy, the radii of the innermost stable circular orbits (ISCOs) of test particles given by analytic exterior space-time geometries have been compared with those given by numerical solutions for neutron stars (NSs) obe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
(119 reference statements)
0
25
0
1
Order By: Relevance
“…Kluźniak et al 1990;Shibata & Sasaki 1998;Pachón et al 2006Pachón et al , 2012Bakala et al 2012;Gutierrez et al 2013). It has been shown that for geodesic motion, these are well described by formulae derived considering NS spacetime approximated by the Hartle-Thorne metric (Hartle & Thorne 1968;Abramowicz et al 2003;Berti et al 2005).…”
Section: Behaviour Of Isco Radius and Ns Compactnessmentioning
confidence: 82%
“…Kluźniak et al 1990;Shibata & Sasaki 1998;Pachón et al 2006Pachón et al , 2012Bakala et al 2012;Gutierrez et al 2013). It has been shown that for geodesic motion, these are well described by formulae derived considering NS spacetime approximated by the Hartle-Thorne metric (Hartle & Thorne 1968;Abramowicz et al 2003;Berti et al 2005).…”
Section: Behaviour Of Isco Radius and Ns Compactnessmentioning
confidence: 82%
“…The importance of the quadrupole moment in the astrophysical context has been emphasized in several works. 9,[11][12][13][14][15] However, most analysis must be performed numerically due to the complexity of the exact metrics. The advantage of considering the HartleThorne approximate solution is that several physical quantities can be calculated analytically which facilitates their study.…”
Section: Geo˙htmentioning
confidence: 99%
“…The non-geodesic corrections to the radial epicyclic frequencies can be generated on the level of tens of percent for oscillating non-slender tori (Šrámková 2005;Blaes et al 2007;Straub & Šrámková 2009), or can do so by assuming a slightly charged internal part of the accretion disc interacting with the external dipole magnetic field of the neutron star when very strong effects can be obtained, on the level of hundred percent or higher Pachon et al 2012). We can consider several diverse possibilities to explain the behaviour of charged accretion discs.…”
Section: Neutron Starsmentioning
confidence: 99%